2007
DOI: 10.1088/0953-2048/20/3/018
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of sheath materials with Mg/B in MgB2conductor fabrication

Abstract: A systematic study on the reactivity of commonly used sheath materials (Ag, Cu, Fe, SS, Ta and Ni) with Mg/B during in situ powder-in-sealed-tube processing of MgB2 superconductor was carried out at different temperatures. Characterization of the samples using XRD, SEM and EDS showed that the heat treatment temperature and type of metal sheath have profound influences on the reactivity. The quantitative data reported here are highly useful for choosing the right sheath material and processing temperature for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The strong drop of critical temperature, T c of MgB 2 in Cu-sheathed wires for heat treatment at 750 • C is consistent with that reported in [24], and also in very good agreement with results reported by Liang et al [11]: this group also presented a complete vanishing of MgB 2 phase in Cu-sheathed wire for heat treatment at 750 • C. These results should be contrasted with those for Mg + 2B samples with only a limited amount of Cu available for alloying. Chen et al [17] reported, for pellets made from (0.2Cu + 0.8Mg + 2B) starting powder, a high T c even for reaction at 800 • C for 1 h; and Kumar et al [31] reported, for Mg + 2B mixed with 10 wt% copper powder enclosed in a stainless steel tube, the maximum volume of MgB 2 formed at a temperature of 825 • C. In the case of Cusheathed wires, the amount of copper available to be reacted with Mg is much higher and this enhances the formation of Cu-Mg intermetallics, often resulting in Mg deficiency and the formation of other phases e.g. MgB 4 at temperatures above 725 • C.…”
Section: Resistivity Versus Temperature Measurementsmentioning
confidence: 99%
“…The strong drop of critical temperature, T c of MgB 2 in Cu-sheathed wires for heat treatment at 750 • C is consistent with that reported in [24], and also in very good agreement with results reported by Liang et al [11]: this group also presented a complete vanishing of MgB 2 phase in Cu-sheathed wire for heat treatment at 750 • C. These results should be contrasted with those for Mg + 2B samples with only a limited amount of Cu available for alloying. Chen et al [17] reported, for pellets made from (0.2Cu + 0.8Mg + 2B) starting powder, a high T c even for reaction at 800 • C for 1 h; and Kumar et al [31] reported, for Mg + 2B mixed with 10 wt% copper powder enclosed in a stainless steel tube, the maximum volume of MgB 2 formed at a temperature of 825 • C. In the case of Cusheathed wires, the amount of copper available to be reacted with Mg is much higher and this enhances the formation of Cu-Mg intermetallics, often resulting in Mg deficiency and the formation of other phases e.g. MgB 4 at temperatures above 725 • C.…”
Section: Resistivity Versus Temperature Measurementsmentioning
confidence: 99%
“…In this study, we illuminate the (usually undesired) by-products and their influence on the superconducting properties of these MgB 2 wires. The results are compared to monofilament MgB 2 /StSt samples as these wires show no or only an extremely small layer of by-products at the filament-sheath interface and a by-product-free filament [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For MgB 2 , the most commonly used sheath materials are Fe and Cu. Cu causes considerable reaction with Mg, degrading the superconductivity [3,4]. So a barrier (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For the Fe sheath the interfacial reaction is less at lower temperatures (<700 • C). However at higher temperatures (>800 • C) Fe also reacts with B, forming the highly resistive interfacial layer Fe 2 B [3,7]. 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%